Pengaruh Kepuasan Layanan dan Customer Experience Terhadap Kepuasan Konsumen di Umayumcha Malang - Alifia Dyah Puspita Ayu; Rizky Kurniawan Murtiyanto; Mohammad Maskan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
In the highly competitive food and beverage (F&B) industry, consumer satisfaction plays a crucial role in ensuring customer loyalty and business sustainability. The increasing popularity of dimsum in Malang has led to the emergence of various dining options, including Umayumcha, a leading dimsum cafe established in 2020. This study aimed to examine the influence of service quality and customer experience on consumer satisfaction at Umayumcha Malang. This explanatory quantitative research examined how service quality and customer experience influenced consumer satisfaction. One hundred respondents were selected through purposive sampling based on three criteria: minimum age of 17 years, at least two previous purchases, and having dining experience at the venue. Data were collected through online questionnaires distributed via social media and were analyzed using multiple linear regression. The research results showed that service quality and customer experience had significant and positive effects on consumer satisfaction. Both independent variables were proven to have significant influence on the dependent variable. Service quality and customer experience explained most of the variance in consumer satisfaction, although there were still other factors that influenced consumer satisfaction beyond the variables studied. Based on the research results, it can be concluded that service quality and customer experience had positive and significant effects on consumer satisfaction at Umayumcha Malang. Therefore, it is recommended that Umayumcha Malang continue to improve service quality and maintain customer experience to enhance consumer satisfaction.